2016
DOI: 10.1080/03630242.2016.1181136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of antenatal care services among adolescent girls and young women in Indonesia

Abstract: Due to the high number of maternal deaths, provision of antenatal care services (ANC) in Indonesia is one of the key aims of the post-Millennium Development Goals agenda. This study aimed to assess the key factors determining use of ANC by adolescent girls and young women in Indonesia. Data from the Indonesia Demographic and Health Survey 2012 were used, with a focus on married adolescent girls (aged 15-19 years, n = 543) and young women (20-24 years, n = 2,916) who were mothers. Bivariate and multiple logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
7
44
0
1
Order By: Relevance
“…This nding re ected the ndings reported in the reviewed literature which is based on African countries [21]. The educated women tend to have greater awareness of the existence of ANC services and the bene ts of using such services [22]. On the contrary, Rurangirwa et al [19] found out that education had no any statistical signi cance.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This nding re ected the ndings reported in the reviewed literature which is based on African countries [21]. The educated women tend to have greater awareness of the existence of ANC services and the bene ts of using such services [22]. On the contrary, Rurangirwa et al [19] found out that education had no any statistical signi cance.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, two studies done in Ethiopia found out that place of residence and education level of the woman contributed to status of ANC attendance for BP checkups [20,21]. Educated women have greater awareness of the existence of ANC services and the bene ts of using such services [22]. Furthermore, socioeconomic status of the woman was also a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests a number of factors may shape the uptake of ANC services across Indonesia, these factors can be conceptualised as individual circumstances, cultural and social dynamics, and community and health care conditions. Within Indonesia, this literature indicates that individual circumstances in uencing ANC uptake may include socioeconomic status, income, age, education and whether a mother is pregnant with her rst child [14][15][16][17]. These factors interact with broader cultural and social factors within which a mother lives to shape ANC uptake [17][18][19][20].…”
mentioning
confidence: 99%
“…These factors interact with broader cultural and social factors within which a mother lives to shape ANC uptake [17][18][19][20]. Further, community and health care conditions are believed to shape accessibility and uptake of ANC services by mothers, with women in urban areas much more likely to achieve adequate ANC visits [14,21]. Shortage of quali ed health providers and overcrowded facilities has also been suggested to in uence ANC uptake [8,15,22].…”
mentioning
confidence: 99%